Pengaruh Latihan Peregangan Otot Intradialisis terhadap Kram Otot - Nurchayati, May; Yulia, Yulia; Sukmarini, Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe the effect of muscle stretching exercises during hemodialysis on muscle cramps. The research method uses an integrative review approach by searching articles using 6 databases, namely ProQuest, ClinicalKey Nursing, Sage Journals, ScienceDirect, Scopus, and ResearchGate. Article searches were carried out from March 5 2024 to March 25 2024. Article searches used the keywords stretching intradialysis, cramps intradialysis, exercises intradialysis, and muscle cramps. Preferred reporting items for systematic reviews and Meta-analysis (PRISMA) were used in the review. Results: From the results of the article search, it was found that muscle stretching exercises during hemodialysis carried out at the end of the HD session were proven to be able to prevent and reduce the intensity of muscle cramps in hemodialysis patients. Conclusion: Muscle stretching exercises performed during hemodialysis have been proven to prevent and reduce the intensity of muscle cramps during hemodialysis Keyword: Muscle cramps, Stretching intradialysis, Muscle stretching